BOPPPS model implementation and students' performance: a systematic literature review - Liu, Jiaying; Omar, Siti Zobidah; Wang, Yang; Xiang, Yue (Frontiers in Education, 2025)
Applications of instructional models are among the key factors in enhancing student performance. While the BOPPPS model is widely implemented, a thorough and systematic evaluation of its impact on student performance remains absent. This systematic review synthesized findings from 19 studies to explore the relationship between the BOPPPS model and student performance. Using the PRISMA, Studies were analyzed for research characteristics, focusing on the use of BOPPPS model, learning subjects, student learning formats, and research theories to better analyze student performance. Specific student-related variables analyzed included academic performance, learning performance, skill tests performance, learning and cognitive ability performance, attendance performance, classroom performance, online performance, and other aspects. The results from the majority of the included studies consistently demonstrated a positive impact of the BOPPPS model on student performance across these diverse areas. To enhance understanding of the BOPPPS model's impact, future research could adopt longitudinal and mixed-method approaches, diversify and expand sample sizes, and explore cross-disciplinary and cross-cultural applications. Integrating new tools with the BOPPPS model is also recommended to further improve learner outcomes.